Measurement of the production cross section ratio sigma(chi b2(1P))/sigma(chi b1(1P)) in pp collisions at √s=8TeV - Khachatryan, V. (2015)
A measurement of the production cross section ratio sigma(chi b2(1P))/sigma(chi b1(1P)) is presented. The chi b1 (1P) and chi b2 (1P) bottomonium states, promptly produced in pp collisions at root s = 8TeV, are detected by the CMS experiment at the CERN LHC through their radiative decays chi b1,2(1P) -> Y(1S) + gamma. The emitted photons are measured through their conversion to e(+) e(-) pairs, whose reconstruction allows the two states to be resolved. The Y(1S) is measured through its decay to two muons. An event sample corresponding to an integrated luminosity of 20.7 fb(-1) is used to measure the cross section ratio in a phase-space region defined by the photon pseudorapidity, vertical bar eta(gamma)vertical bar < 1.0; the Y(1S) rapidity, vertical bar y(Y)vertical bar < 1.5; and the Y(1S) transverse momentum, 7 < p(T)(Y) < 40 GeV. The cross section ratio shows no significant dependence on the.(1S) transverse momentum, with a measured average value of 0.85 +/- 0.07 (stat + syst) +/- 0.08 (BF), where the first uncertainty is the combination of the experimental statistical and systematic uncertainties and the second is from the uncertainty in the ratio of the chi b branching fractions. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.